2023
DOI: 10.1039/d3mh00024a
|View full text |Cite
|
Sign up to set email alerts
|

Chiral-induced spin selectivity in biomolecules, hybrid organic–inorganic perovskites and inorganic materials: a comprehensive review on recent progress

Abstract: The two spin states of electrons are degenerate in nonmagnetic materials. Chiral-induced spin selectivity (CISS) effect provides a new strategy for manipulating electron’s spin and a deeper understanding of spin...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 209 publications
(381 reference statements)
0
12
0
Order By: Relevance
“…The studied crystals indeed display interesting effects resulting from combining paramagnetic ions and chiral lattices. 21 Recently other organic/inorganic systems 22,23 were shown to also have interesting spin-related properties and together with the MOC, they expand the variety of organic molecule-based solids that can serve in spintronics.…”
Section: Discussionmentioning
confidence: 99%
“…The studied crystals indeed display interesting effects resulting from combining paramagnetic ions and chiral lattices. 21 Recently other organic/inorganic systems 22,23 were shown to also have interesting spin-related properties and together with the MOC, they expand the variety of organic molecule-based solids that can serve in spintronics.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] CISS effect provides the possibility to control both spin and charge degrees of freedom, which is the fundament of spintronic devices. To date, several monographic reviews have summarized the research progress of chiral spintronics in perovskites, [ 3,14,136–138 ] so we briefly recall some representative papers about the spintronic properties of chiral PeNCs in this section to provide readers with further insights.…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…[3] CISS effect provides the possibility to control both spin and charge degrees of freedom, which is the fundament of spintronic devices. To date, several monographic reviews have summarized the research progress of chiral spintronics in perovskites, [3,14,[136][137][138] so we briefly recall some representative papers about the spintronic properties of chiral PeNCs in this section to provide readers with further insights. In 2021, Kim et al pioneered the fabrication of spin-LEDs with a ±2.6% circularly polarized electroluminescence at room temperature in a two-layered perovskite heterostructure, in which the 2D chiral perovskites served as the CISS layer and the 3D PeNCs functioned as the emitting layer.…”
Section: Chiral Spintronicsmentioning
confidence: 99%
“…1,2 It has been found that inorganic materials endowed with chirality generate optical, electrical, magnetic, and other special properties, which can have wide applications in chiral sensing, catalysis, and devices. 3–9 Currently, numerous chiral inorganic crystals, including metals, semiconductors, ceramics, and inorganic salts, with different chiral structures, sizes and surface properties, have been synthesized for their interesting chiral response. 10–15…”
mentioning
confidence: 99%
“…1,2 It has been found that inorganic materials endowed with chirality generate optical, electrical, magnetic, and other special properties, which can have wide applications in chiral sensing, catalysis, and devices. [3][4][5][6][7][8][9] Currently, numerous chiral inorganic crystals, including metals, semiconductors, ceramics, and inorganic salts, with different chiral structures, sizes and surface properties, have been synthesized for their interesting chiral response. [10][11][12][13][14][15] As one of the spinel ferrites, nickel ferrite (NiFe 2 O 4 ) is highly regarded for its unique properties and promising applications, including in sensors, recording media, supercapacitors, and actuators.…”
mentioning
confidence: 99%